The Relationship of Subjective Well-being with Regulatory and Personality Characteristics in the Primary School Age Children - Fomina T.G.; Eftimova O.V.; Morosanova V.I. (Психолого-педагогические исследования, 2018)
The study on relationship between conscious self-regulation, intrapersonal characteristics, and subjective well-being of younger schoolchildren (N = 156, age 10-11 years) made it possible to reveal and analyze significant links of the regulatory characteristics and personality factors (the Big Five model) with a cognitive parameter of subjective well-being in three spheres: family, school and self-attitude. Morosanova’s Self-Regulation Profile Questionnaire – Junior ), Russian version of the «Big Five Questionnaire – Children BFQ-C (S.B. Malykh , T.N. Tikhomirova, G.M. Vasin) » and Russian adaptation of Multidimensional Students Life Satisfaction Scale MSLSS (T.O. Gordeeva, E.N. Osin) was used. The results analysis provided for identifying significant regulatory and intrapersonal predictors of subjective well-being specific to primary school age children. The level of certain regulatory features development, as well as the general level of conscious self-regulation of educational activity proved to be significant factors of the schoolchildren subjective well-being